Cosmos in a painting: reflections on Judeo-Christian creation symbolism - Vaz da Silva, F. (2011)
This paper addresses the cosmological assumptions underpinning an enigmatic variation on the Madonna-and-Child image, in which the Child Jesus appears as a dragon slayer. In order to evoke the mental landscapes that could make sense of this composition, the discussion visits folklore, Christian art, and the Scriptures. By and by, it finds that the enigmatic image analogizes the story of Genesis and an ancient dragon-fight myth, so that Mary’s victory over the ancient serpent both redeems the fault of Eve and reflects God’s primordial victory over the dragon. The image also draws on the traditional analogy between the Father’s victory over marine chaos and the Son’s overcoming of the Ancient Law, which allows treating the birth, baptism, and resurrection of Jesus as so many variations on a single theme. The discussion suggests that the enigmatic composition draws on a leitmotiv of scriptural writings – the defeat of the chthonic dragon, and the correlative victory of the celestial bird – and thus provides a striking example of symbolic condensation in a painting.